Respiratory morbidity in children who had undergone primary repair of esophageal atresia with tracheo esophageal fistula in a tertiary care centre in India - Kumar, Madhan; Varkki, Sneha Deena; Karl, Sampath; Bal, Harshjeet Singh; Irodi, Aparna; John, Mary; Rathi, Alok (International Journal of Contemporary Pediatrics, 2021)
Background: Objective of the study was to assess the prevalence of respiratory and related GI morbidity in children who had undergone repair of oesophageal atresia/tracheoesophageal fistula (TEF) in the neonatal period. Methods: Patients operated during the period 2008–2015 were evaluated in 2017 by clinical evaluation, radiological imaging (chest X-ray, barium swallow study and high-resolution computed tomographic scan) and laryngoscopy examination. Results: Of the 50 neonates who underwent primary repair of TEF during the 8 year period, 39 were discharged successfully. Twenty-six of them at a Mean age of 64 months were included in the study. At the time of assessment, 65% of subjects registered body mass index (BMI) less than 10th centile. Abnormal respiratory system findings in 63% and digital clubbing in 27% were noted. Unilateral asymptomatic vocal cord was demonstrated in 7.7%. Radiological evaluation showed abnormal oesophageal motility/reflux in 54% and bronchiectasis in 19%. In addition, 62% had needed hospitalization for recurrent pneumonia in infancy. Environmental smoke exposure was reported in 38% and 73% had no regular follow up with a pediatrician. Conclusions: This comprehensive evaluation of respiratory morbidity in children who had been operated for TEF in the neonatal period, demonstrated a high prevalence of reported respiratory morbidity in the first year of life. Poor nutritional outcomes and abnormal respiratory system examination were observed in a significant proportion. One-fifth of these patients had already developed bronchiectasis by a mean age of 75.4 months. Asymptomatic unilateral vocal cord palsy was another important finding.